2010
DOI: 10.1021/nl103015w
|View full text |Cite
|
Sign up to set email alerts
|

Probing Charge Transfer at Surfaces Using Graphene Transistors

Abstract: Graphene field effect transistors (FETs) are extremely sensitive to gas exposure. Charge transfer doping of graphene FETs by atmospheric gas is ubiquitous but not yet understood. We have used graphene FETs to probe minute changes in electrochemical potential during high-purity gas exposure experiments. Our study shows quantitatively that electrochemistry involving adsorbed water, graphene, and the substrate is responsible for doping. We not only identify the water/oxygen redox couple as the underlying mechanis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

22
313
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 298 publications
(336 citation statements)
references
References 26 publications
22
313
0
1
Order By: Relevance
“…19 More recently, Levesque et al identified the water/oxygen redox couple as the underlying mechanism responsible for charge doping in graphene-SiO 2 and graphene-parylene FETs. 20 However, in the latter work, the choice of the geometry of the sample was chosen in order to preclude strong bonding from playing an important role in the measurement so as to isolate the effect of gas interaction. This is fundamentally different from the epitaxial graphene case, where the interaction with the substrate is not only inevitable, but plays an integral part in the determination of the properties of the active layer.…”
Section: à2mentioning
confidence: 99%
“…19 More recently, Levesque et al identified the water/oxygen redox couple as the underlying mechanism responsible for charge doping in graphene-SiO 2 and graphene-parylene FETs. 20 However, in the latter work, the choice of the geometry of the sample was chosen in order to preclude strong bonding from playing an important role in the measurement so as to isolate the effect of gas interaction. This is fundamentally different from the epitaxial graphene case, where the interaction with the substrate is not only inevitable, but plays an integral part in the determination of the properties of the active layer.…”
Section: à2mentioning
confidence: 99%
“…[12][13][14] Second, it has been shown that impurities on graphene that contain states near the Dirac point can be charged and discharged as the graphene Fermi level is varied via the applied gate bias. 15,16 This charging and discharging process cause the background doping to have a gate dependence (as impurities are turned 'on' and 'off') , and thus alter the expected gate voltage vs. carrier density dependence.…”
Section: Determination Of Carrier Density Of Graphene Sheetmentioning
confidence: 99%
“…[ 31] In the conditions used here, this unintentional doping induces a blue shift by~10 cm À1 for the monolayer relative to islands of bilayers and multilayers (i.e. the monolayer is p doped).…”
Section: Examples Of Structural Analysis Of Nanomaterialsmentioning
confidence: 99%